Evaluasi Kesuburan Tanah Ultisol pada Pertanaman Karet di Kecamatan Cempaka Kota Banjarbaru, Provinsi Kalimantan Selatan - Byanra Firas Daksina; Anna Maria Makalew; Bambang Fredrickus Langai (Universitas Lambung Mangkurat, 2021)
Rubber is one of the mainstay commodity plantations that plays a role in the national economy, including in the economy of South Kalimantan Province. The purpose of this study was to determine the fertility status of Ultisols in rubber plantations in Cempaka District, Banjarbaru City, South Kalimantan Province. Using a survey method, the rubber planting location was determined through purposive sampling. Observation variables include pH H2O 1:5; cation exchange capacity, CEC (me / 100 g) and base saturation, KB (%) 1N NH4OAc extract pH 7.0; P-total (mg / 100g) and K-total (mg / 100g) 25% HCL extract; and the C-organic (%) Walkey and Black method. The soil fertility status was determined according to PPT, 1995. The results showed that Ultisol soil in rubber plantations in Cempaka District, Banjarbaru City, South Kalimantan Province had low fertility status. This low fertility status is due to the nature of the soil which has acid criteria, a pH of 4.90; KTK is classified as medium criteria, amounting to 18.78 me / 100 g; KB is classified as very low, amounting to 9.99%; P-Total classified as low, a number of 4.63 (mg / 100g); K-Total classified as low, worth 16.32 (mg / 100g); and C- Organic which is included in the moderate criteria, amounting to 2.11%. This study revealed that the main inhibiting factors for soil fertility in rubber plantation in Cempaka District were pH, KB, P-total, and K-Total. To improve soil fertility status, calcification, addition of organic matter, and fertilization can be carried out.